Levels of Reality in Science and Philosophy Re-examining the Multi-level Structure of Reality - Ioannidis, Stavros; Vishne, Gal.; Hemmo, Meir.; Shenker, Orly. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers a unique perspective on one of the deepest questions about the world we live in: is reality multi-leveled, or can everything be reduced to some fundamental 'flat' level? This deep philosophical issue has widespread implications in philosophy, since it is fundamental to how we understand the world and the basic entities in it. Both the notion of 'levels' within science and their ontological implications are issues that are underexplored in the philosophical literature. The volume reconsiders the view that reality contains many levels and opens new ways to understand the ontological status of the special sciences. The book focuses on major open questions that arise at the foundations of cognitive science, cognitive psychology, brain science and other special sciences, in particular with respect to the physical foundations of these sciences. For example: Is the mental computational? Do brains compute? How can the special sciences be autonomous from physics, grounded in, or based on, physics and at the same time irreducible to physics? The book is an important read for scientists and philosophers alike. It is of interest to philosophers of science, philosophers of mind and biology interested in the notion of levels, but also to psychologists, cognitive scientists and neuroscientists investigating such issues as the precise relation of the mental to the underlying neural structures and the appropriate approach to study it.
Chapter 1. Introduction (Meir Hemmo, Stavros Ioannidis, Orly Shenker, Gal Vishne) -- Chapter 2. Phenomenality and Accessibility of Conscious Experience (Katalin Balog) -- Chapter 3. Levels of Reality and Levels of Description (Yemima Ben-Menahem) -- Chapter 4. Levels of Reality and the Method of Metaphysics (Michael Esfeld) -- Chapter 5. Can the Extended Current-Physics Reply Avoid Hempel's Dilemma? (Erez Firt) -- Chapter 6. How Context Can Determine the Identity of Physical Computation (Nir Fresco) -- Chapter 7. The Incremental Chain of Being (John Heil) -- Chapter 8. How to Carve Nature at its Joints (Meir Hemmo & Orly Shenker) -- Chapter 9. Fleeing from Flat Physicalism (Carl Hoefer) -- Chapter 10. Is Mechanistic Investigation Reductive? (Arnon Levy) -- Chapter 11. Levels in the Mentaculus (Barry Loewer) -- Chapter 12. Structural Interpretation and Reductionism (Holger Lyre) -- Chapter 13. Physicalism: Flat or Egalitarian? (Gualtiero Piccinini) -- Chapter 14. Levels of Mechanism: Constitution vs Causation (Stathis Psillos & Stavros Ioannidis) -- Chapter 15. Rethinking the Unity of Science Hypothesis: Levels, Mechanisms, and Realization (Lawrence Shapiro) -- Chapter 16. Supervenience, Levels, and Probability (Elliott Sober).
Keywords: Science-Philosophy.; Cognitive psychology; Philosophy of mind; Biology-Philosophy.; Metaphysics; Philosophy of Science; Cognitive Psychology; Philosophy of Mind; Philosophy of Biology; Metaphysics